Analysis of management of zakat, infaq, alms (zis) funds in improving the economy of the dhuafa - Kahfi, Muhammad Shohibul; Imsar, Imsar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Study this aim for analyze method LAZ WASHAL Charity North Sumatra in raising ZIS funds and to analyze how method distribution ZIS by LAZ WASHAL in increase economy poor people, to analyze how the strategy is carried out by LAZ WASHAL in improving the economy of the poor. The methodology of this research is use study qualitative with approach descriptive. Technique data collection was carried out by in-depth interviews. While the technique analysis data conducted with method reduction, presentation data and withdrawal conclusion. Results study this show that method collect fund Zakat, infaq, and Alms is with three method that is via social media ,via transfer between tub , and come direct to office LAZ WASHAL Charity North Sumatra. Efforts in the distribution of ZIS at LAZ WASHAL Charity North Sumatra was carried out by means of a direct survey of mustahik who were program for given help, with choose two category that is worthy assisted and deserving of special assistance. LAZ WASHAL's strategy Charity in North Sumatra is by monitoring business developments that conducted by mustahik which given fund ZIS with method supervise and guide if trouble occurs in developing his efforts